Factor Analysis: An Instrument for Selection of Social Performance Factors - Hornungová, Jana (Universidad Pablo de Olavide, 2014)
The article is focused on the identification of social performance factors. For this purpose was used multidimensional statistical method – factor analysis. The basic set for the selection of indicators, was the concept (and the social tool) of Corporate Social Responsibility, subsequently, was constructed the questionnaire. Empirical research was attended by 32 companies, from the area Information and Communication Activities (CZ-NACE, section J), with the number of employees over 250. The aim of the factor analysis was selection of significant indicators and performance factors for selected area from the input database. On the basis of the paper, there were evaluated three social factors from the area of working environment and two social factors from the area of local community. The understanding of their application into the internal management shall be necessary prior to company's decision regarding the measures of key performance indicators.

The article is focused on the identification of social performance factors. For this purpose was used multidimensional statistical method – factor analysis. The basic set for the selection of indicators, was the concept (and the social tool) of Corporate Social Responsibility, subsequently, was constructed the questionnaire. Empirical research was attended by 32 companies, from the area Information and Communication Activities (CZ-NACE, section J), with the number of employees over 250. The aim of the factor analysis was selection of significant indicators and performance factors for selected area from the input database. On the basis of the paper, there were evaluated three social factors from the area of working environment and two social factors from the area of local community. The understanding of their application into the internal management shall be necessary prior to company's decision regarding the measures of key performance indicators.
Factor Analysis: An Instrument for Selection of Social Performance Factors
Keywords: Business Management; Performance; Indicators; Factor Analysis; Business Management; Performance; Indicators; Factor Analysis